Immersive poetry learning: a field study with middle school students - Reynaert, Vincent; Possik, Jalal; Demarey, Catherine; Kieken, Danny; Abert, Benoit; De Witte, Benjamin (Frontiers in Education, 2024)
IntroductionThe field of poetry learning is currently facing significant challenges, primarily due to a lack of motivation and interest among students. This has resulted in educators encountering difficulties in identifying suitable educational alternatives. To address the latter issue, immersive learning has emerged as a potential solution, as it has been demonstrated to enhance motivation and learning outcomes in a multitude of fields.MethodsIn light of the aforementioned considerations, this field study seeks to examine the potential of virtual reality (VR) tools in enhancing the memorization of poetry by increasing the engagement of the participants. The study concentrated on the acquisition of a French poem by a group of middle school students. A virtual environment has been developed for this purpose, tailored to the poem in question. The experimental design included a pretest, segmented learning sessions, a posttest, and a retention test. To evaluate student engagement, both motivation and sense of presence were measured using Likert-scale questionnaires, while memorization performance was assessed through a scoring system based on recall accuracy.ResultsThe findings reveal that the VR group demonstrated significantly higher motivation than the control group, with a mean difference of 12.626 on a 7-point Likert scale (six items), indicating that VR is a notably more effective tool for enhancing motivation in poetry learning than traditional methods. Additionally, the VR group reported a significantly stronger sense of presence, with a mean difference of 6.111 on the same questionnaire scale, further suggesting that VR enhances students’ sense of immersion in the learning experience. These results indicate that students using VR exhibited higher levels of overall engagement than those in the control group.DiscussionHowever, this increased engagement did not lead to improved memorization outcomes, as there was no significant difference in recall accuracy between the two groups. A potential explanation for this discrepancy is the “novelty effect” of VR, which may have distracted students from focusing fully on the memorization task. The implications of integrating VR in educational settings are thus discussed.